The Puzzling Potential of Carbon Nanomaterials: General Properties, Application, and Toxicity - Jović, Danica (Nanomaterials (Basel), 2020)
Being a member of the nanofamily, carbon nanomaterials exhibit specific properties that mostly arise from their small size. They have proved to be very promising for application in the technical and biomedical field. A wide spectrum of use implies the inevitable presence of carbon nanomaterials in the environment, thus potentially endangering their whole nature. Although scientists worldwide have conducted research investigating the impact of these materials, it is evident that there are still significant gaps concerning the knowledge of their mechanisms, as well as the prolonged and chronic exposure and effects. This manuscript summarizes the most prominent representatives of carbon nanomaterial groups, giving a brief review of their general physico-chemical properties, the most common use, and toxicity profiles. Toxicity was presented through genotoxicity and the activation of the cell signaling pathways, both including in vitro and in vivo models, mechanisms, and the consequential outcomes. Moreover, the acute toxicity of fullerenol, as one of the most commonly investigated members, was briefly presented in the final part of this review. Thinking small can greatly help us improve our lives, but also obliges us to deeply and comprehensively investigate all the possible consequences that could arise from our pure-hearted scientific ambitions and work.